Problem-Based Learning Model Using Geogebra Application: Students Motivation to Learn Translation Material of High School - Nurfadila, Nurfadila; Hasbi, Muh.; Puspawati, Ni Made (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
This study aims to describe the application of the Problem-Based Learning (PBL) model with the help of the GeoGebra application to increase students' learning motivation for geometric transformation material, especially translation. This study is a form of classroom action research carried out in two cycles in class XI E of High School 4 Palu involving 35 students. Each cycle consists of planning, implementation, observation, and reflection steps. In cycle I, the material is related to translation to points, while in cycle II, it is related to translation to lines. Data were collected through a learning motivation questionnaire and observation sheets, which were analyzed descriptively. The results indicated that students' learning motivation increased from cycle I to cycle II. In cycle I, only 6 students (17.1%) were included in the strong motivation category, while 11 students (31.5%) were included in the low category. After the improvement in Cycle II, the number of highly motivated students increased to 15 (42.8%), while those in the low group decreased to only 2 (5.8%). Observational data shows increased student engagement and enjoyment in learning. Consequently, the implementation of the GeoGebra-assisted PBL paradigm has proven successful in increasing motivation in mathematics learning.